Globalization, Inequality, and Redistribution:Theory and Evidence - Giray Gozgor; Priya Ranjan (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper constructs a simple theoretical model to study the implications of globalization for inequality and redistribution. It shows that when globalization increases inequality, a policymaker interested in maximizing the sum of welfares of all agents increases redistribution. Empirically, the paper examines the effects of globalization on inequality and redistribution in a panel data set of 140 countries for the period from 1970 to 2012. It finds that both inequality and redistribution have been increasing with globalization. The results are robust to the inclusion of many different controls and the exclusion of outliers.
Keywords: F68; D63; H11; 330; globalization; income inequality; redistributive policies